Bidirectional association between functional disability and multimorbidity among middle-aged and older adults in Thailand - Pengpid, Supa; Peltzer, Karl; Anantanasuwong, Dararatt (Frontiers in Public Health, 2022)
Objectives The purpose of this study was to assess the bidirectional association between multimorbidity (MM) and functional disability among middle-aged and older adults in a longitudinal study in Thailand. Methods We analyzed longitudinal data of participants aged 45 years and older from two consecutive waves (in 2015 and 2017) of the Health, Aging, and Retirement in Thailand (HART). Functional disability was assessed with a 4-item activity of daily living (ADL) scale. Logistic regression analysis was conducted to assess the association between baseline functional disability and incident MM (≥2), and baseline morbidity and incident functional disability. Results The results indicate that a total of 1,716 individuals without morbidity at baseline and 3,529 without functional disability at baseline were included. At follow-up, 16.7 and 20.0% of functional disability cases and 7.1 and 3.6% of nonfunctional disability cases developed 2 morbidities and 3 or more morbidities, respectively, and 6.6% of MM cases and 4.0% of non-MM cases developed a functional disability. In the final logistic regression model adjusted for education, income, age, marital status, sex, smoking tobacco, body mass index (BMI), alcohol use, physical activity, and social engagement, functional disability at baseline was positively associated with incident MM (≥2) (adjusted odds ratio [aOR]: 2.58, 95% CI: 1.42–4.72), and MM (≥3) at baseline was positively associated with incident functional disability (aOR: 1.97, 95% CI: 1.13–3.43). Conclusion Multimorbidity and functional disability were bidirectionally associated.